2019
DOI: 10.1186/s13059-019-1890-1
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa accessory genome elements influence virulence towards Caenorhabditis elegans

Abstract: BackgroundMulticellular animals and bacteria frequently engage in predator-prey and host-pathogen interactions, such as the well-studied relationship between Pseudomonas aeruginosa and the nematode Caenorhabditis elegans. This study investigates the genomic and genetic basis of bacterial-driven variability in P. aeruginosa virulence towards C. elegans to provide evolutionary insights into host-pathogen relationships.ResultsNatural isolates of P. aeruginosa that exhibit diverse genomes display a broad range of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 63 publications
(78 reference statements)
2
36
0
Order By: Relevance
“…While individual AGEs showed low importance in model predictions, it is relevant that all of the 10 most important AGEs included in our model were associated with low virulence. This supports the earlier finding that the presence of specific P. aeruginosa accessory genes can reduce virulence in C. elegans and that active CRISPR systems, which would limit acquisition of foreign DNA and new AGEs, are associated with higher virulence in that model (16). While certain AGEs enhance virulence (15), many AGEs (e.g., parasitic phages, plasmids, or ICEs) may decrease virulence through mechanisms such as dysregulation of regulatory networks, insertion into important genes, or imposition of an additional metabolic burden.…”
Section: Discussionsupporting
confidence: 90%
“…While individual AGEs showed low importance in model predictions, it is relevant that all of the 10 most important AGEs included in our model were associated with low virulence. This supports the earlier finding that the presence of specific P. aeruginosa accessory genes can reduce virulence in C. elegans and that active CRISPR systems, which would limit acquisition of foreign DNA and new AGEs, are associated with higher virulence in that model (16). While certain AGEs enhance virulence (15), many AGEs (e.g., parasitic phages, plasmids, or ICEs) may decrease virulence through mechanisms such as dysregulation of regulatory networks, insertion into important genes, or imposition of an additional metabolic burden.…”
Section: Discussionsupporting
confidence: 90%
“…Still, it is relevant that all of the ten most important AGEs included in our model were associated with low virulence. This supports the earlier finding that P. aeruginosa accessory genes can reduce virulence in C. elegans and that active CRISPR systems, which would limit acquisition of foreign DNA and new AGEs, are associated with higher virulence in that model 16 . While certain AGEs enhance virulence 15 , the majority of AGEs (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…We recently mined the accessory genome and identified multiple novel factors important in virulence in a mouse model of bacteremia 15 . Conversely, a study using a Caenorhabditis elegans model identified several P. aeruginosa accessory genes whose presence reduced virulence 16 . Further, the presence of active CRISPR systems was associated with increased virulence 16 , supporting the hypothesis that many horizontally transferred elements are genetic parasites with respect to the host bacterium 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Pseudomonas aeruginosa, accessory gene elements have enhanced the virulence toward invertebrate Caenorhabditis elegans [6]. GIs' another class of accessory gene elements contribute to the evolution and adaptation to the niche.…”
Section: Introductionmentioning
confidence: 99%